Hubungan Persepsi Terhadap Metode Pembelajaran Daring Dengan Motivasi Belajar Mahasiswa Program Studi Kedokteran Universitas Batam Selama Pandemi Covid-19 - Isramilda Isramilda; Kasih Purwati; Elisa Indriany Manik (Universitas Batam, 2022)
Background:Covid-19 is an infectious disease caused by a newly discovered type of coronavirus. Therefore, to minimize and break the chains of Covid-19 spreadness, Indonesian government issued a policy by enforced the Big Scale Social Restrictions, where doing online learning method is one example of the implementation. Changes in learning methods, especially as a medical students, greatly affect the learning process, including student perceptions and student learning motivation. Methods:This is an observational analytic research using a cross-sectional approach conducted at the Faculty of Medicine Batam University in November 2021. A total of 90 students were analyzed through a simple random sampling method. The spearman test was used to determine the correlation between student perceptions to online learning methods and student learning motivation. Results:The spearman test result showed a significant correlation between student perceptions to online learning methods and student learning motivation, with p value = 0,000 (p<0,05). Conclusion:According to the results of this research, it can be concluded that there is a correlation of perception to online learning methods with student learning motivation in Medical Study Program Students In Batam University.